Multifunctional mesoporous silica nanoparticles for drug loading and release - Ng, Yu Ning (2015)
The usage of mesoporous silica nanoparticles in drug delivery systems has garnered a lot of attention in the recent years due to its unique morphology and physiochemical properties. Many characteristics of these nanoparticles affect the effectiveness of their usage as drug delivery carriers. Although there have been many studies conducted regarding mesoporous silica nanoparticles and its uses, the effects of size and surface charges were not explored in great detail. Thus, the objective of this study is to analyze the effects of size and surface charges of these nanoparticles on the efficiency of cellular uptake. This was done by synthesizing and functionalizing the nanoparticles, followed by testing them using various characterization techniques, such as transmission electron microscopy, Fourier transform infrared spectroscopy, zeta potential, confocal laser scanning microscopy, and flow cytometry. Both qualitative and quantitative results showed that the cellular uptake efficiency was dependent on the size and surface charge present on the mesoporous silica nanoparticles. MTT assay test was also carried out to prove the non-cytotoxicity of these nanoparticles. This test proved the suitability of these nanoparticles for biomedical uses. From the results obtained, it is evident that smaller, and positively charged mesoporous silica nanoparticles were the most favourable for high cellular uptake efficiency. These findings would contribute in the engineering of improved drug delivery systems and devices for future biomedical applications.